Pharmacare 2019 - Orlando, Valentina (Pharmàkon, 2021)
This volume aims to offer an effective and comprehensive summary of the data on consumption and expenditure of drugs dispensed by the Regional Health Service (SSR) of Campania region under health care agreements during the year 2019. By using information supplied by a database covering a population of about six million inhabitants, a correlation has been drawn between the prevalence of diseases in the area and the corresponding use of drugs, suggesting at the same time useful interpretations of the main factors influencing the variability in prescriptions. A thorough analysis was then conducted on the prescribing profiles of the main therapeutic categories, particularly focused on polypharmacy regimens in the over-65s, gender differences in medication use, and medication use profiles in patients with COVID-19. A detailed overview of medication use in terms of expenditure, volume and type within the region has thus been created, which aims to be a monitoring tool to support decision-makers, useful both for the planning of public health interventions, and for the identification of potential areas of improvement in these contexts.